The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1155/2017/4639202
|View full text |Cite
|
Sign up to set email alerts
|

CT Scanning in Identification of Sheep Cystic Echinococcosis

Abstract: Objective We aim to determine the efficiency of CT in identification of cystic echinococcosis in sheep. Methods Fifty-three sheep with liver cysts confirmed by ultrasonography were subject to CT scan to evaluate the number, size, and type of the cysts in liver and lung, confirmed using necropsy. The correlation of numbers between liver cysts and lung cysts was calculated using Pearson analysis. Results Necropsy indicated a 98% consensus on size, location, number, and activity compared with CT scan. The viable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Besides the sensitivity, specificity, and accuracy of PCA‐SVM methods showed that these indexes were better than some commonly used methods for diagnosing CE in sheep, for instance, B‐ultrasound (sensitivity 75%–88%, specificity 70%–76%) [53], and ELISA detection (sensitivity 55%–60%, specificity 67%–70%) [54]. There were some drawbacks in the B‐ultrasound detection technology, such as the need to trim the sheep wool, the difficulty in operation, the need for expensive imaging equipment, and professional imaging physicians [55]. Serological testing was difficult to standardize and has low sensitivity and specificity [54].…”
Section: Resultsmentioning
confidence: 99%
“…Besides the sensitivity, specificity, and accuracy of PCA‐SVM methods showed that these indexes were better than some commonly used methods for diagnosing CE in sheep, for instance, B‐ultrasound (sensitivity 75%–88%, specificity 70%–76%) [53], and ELISA detection (sensitivity 55%–60%, specificity 67%–70%) [54]. There were some drawbacks in the B‐ultrasound detection technology, such as the need to trim the sheep wool, the difficulty in operation, the need for expensive imaging equipment, and professional imaging physicians [55]. Serological testing was difficult to standardize and has low sensitivity and specificity [54].…”
Section: Resultsmentioning
confidence: 99%
“…Mao et al in 2017 determined the efficiency of CT scan modality in the identification of CE in sheep. The results indicated that CT is a suitable tool for determining the size and type of CE cysts in the liver and lungs of sheep [ 66 ]. The utilization of CT scans for detecting and characterizing CE cysts is very limited to humans and sheep.…”
Section: Discussionmentioning
confidence: 99%
“…In small animals, except for the CNS, CT usually represents a second level modality for studying the skeleton, particularly the axial one (skull and spine), the thorax and the abdomen [3] . The use of CT is also described for equine [19] , cattle [20] , goat [21] , sheep [22] , swine [23] , avian and chelonian [11] , reptiles [24] , rabbit and rodents [25] . As in human medicine, CT can be used as bone densitometer [26] .…”
Section: Computed Tomographymentioning
confidence: 99%